A molecular view of onychophoran segmentation. Issue 3 (May 2017) - Janssen, Ralf
Abstract: This paper summarizes our current knowledge on the expression and assumed function of Drosophila and (other) arthropod segmentation gene orthologs in Onychophora, a closely related outgroup to Arthropoda. This includes orthologs of the so-called Drosophila segmentation gene cascade including the Hox genes, as well as other genetic factors and pathways involved in non-drosophilid arthropods. Open questions about and around the topic are addressed, such as the definition of segments in onychophorans, the unclear regulation of conserved expression patterns downstream of non-conserved factors, and the potential role of mesodermal patterning in onychophoran segmentation. Highlights: Current knowledge on the genetic mechanisms underlying onychophoran segmentation is summarized. Gap gene orthologs are analyzed for the first time in an onychophoran species. Problematic questions concerning onychophoran segmentation are discussed.